Convenience sampling for acceptability and cata measurements may provide inaccurate results : a case study with fruit-flavored powdered beverages tested in Argentina, Spain and U.S.A. - Cardinal, Paula (2015)
Fil: Cardinal, Paula. Comisión de Investigaciones Científicas; Argentina